Pengaruh Media Exposure, Leverage, dan Profitabilitas Terhadap Pengungkapan Emisi Karbon pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Aliyyah Fitriyani; Virna Sulfitri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to test and analyze the effect of Media Exposure, Leverage, and Profitability on Disclosure of carbon emissions. The research was conducted on energy sector companies listed on the Indonesia Stock Exchange (IDX) using secondary data obtained from annual reports and sustainability reports during the 2021-2023 period using purposive sampling technique. The amount of data in this study was 156 observations. The analysis method used is panel data regression which is processed using EViews12. The results showed that Media Exposure has a positive effect on Carbon Emissions Disclosure, while Leverage and Profitability have no effect on Carbon Emissions Disclosure.